Mild hypothermia reduces expression of Fas/FasL and MMP-3 after cerebral ischemia-reperfusion in rats - Zhao, Jingkun (Mashhad University of Medical Sciences, 2014)
OBJECTIVE(S): To investigate the effects of local mild hypothermia on the expression of Fas, FasL and MMP-3 after cerebral ischemia-reperfusion in rats. MATERIALS AND METHODS: Male Wistar rats were divided into sham-operated group (Sham), normothermia group (NT), and hypothermia group (HT). MCAO/R model was established by Longa’s method, and reperfusion was allowed after 2 hr occlusion. Mild hypothermia (33±0.5°C) for 6 hr was initiated at the start of reperfusion. Immunohistochemistry was performed to determine expression Fas, FasL, and MMP-3. RESULTS: Infarct volume was reduced in the hypothermia group (18.43±4.23%) compared with the normothermia group (24.76±5.76%) (P<0.05). In mild hypothermia group, numbers of Fas-positive and MMP-3 positive cells were significantly less than those of normothermia group (P<0.05). Neurological functional scores of mild hypothermia were significantly improved (P<0.05). CONCLUSION: Mild hypothermia decreases infarct volume after cerebral ischemia-reperfusion, reduces Fas and MMP-3 expression, but increases FasL in cerebral ischemia-reperfusion rats.